Comparative Study On Nursing Of Different Strains Of Tilapia (Oreochromis niloticus) In Bangladesh (International Journal of Natural Sciences, 2016)
This study was conducted to investigate and compare the growth performance of four Tilapia strains in hapa nursing with the aim to find out the best strain of tilapia. The research was conducted by four treatments with five replicates each. The tilapia fry were collected from, BFRI source from BFRI HQ, Mymensingh stocked in Treatment-1; unknown source from Hi-Tech Tilapia Hatchery Dagoanbhuiya, Feni in Treatment-2, Philipine strain from Green Field Tilapia Hatchery, Laxmipur in Treatment-3 and fry from Breeding Cohort, Sonar Bangla Hatchery, Bamna, Barguna in Treatment-4. The Individual stocking weight (g) of fry was average 0.01g. The fries were stocked in 12 hapa at same stocking density of 1200 fish/m2. Each of the hapa was 2m × 1m × 1m size and fixed in an earthen ponds. Supplementary feed with 31.29% of protein level consisting of rice bran (25%), mustard oil cake (15%), wheat flour (30%) and fish meal (30%) was given at the rate of 40% of their body weight per day manually, four times a day at the beginning of the experimental period and reduced to 25% of their body weight and continued up to harvesting period. The results showed that fry of Treatment-4 strain was the best strain and had significantly (p < 0.05) higher final mean body weight (FMBW), mean body weight gain (MBWG), specific growth rate (SGR) (9.75%), gross yield (GY) (2.13) and Net yield (NY) (2.12) than the Treatment-1 , Treatment-2 strains and Treatemnt-3 strain. Treatment-4 strain had the fastest growth rate, whereas the lowest performing strain was that from Treatment-2. We also analyzed survival rate of the fish from stocking to harvest, survival rate was highest in Treatment-4 strain (80%) where lowest is Treatment-3. Treatment-4 stain also showed the best feed conversion ratio (FCR) 1.62 than others. Considering the overall performance it can be concluded that tilapia strain collected from Breeding Cohort source is best among the four strains. However, further research may still be needed to compare more strains from different water body to evaluate the genetic potential for Tilapia.International Journal of Natural Sciences (2015), 5(2) 98-106